Scientific writing and the contentfulness of Subject Themes. How science was explained to (lay) audiences - Martinez-Insua, Ana Elina (Journal of pragmatics, 2019)
This study forms part of an ongoing investigation of the contentfulness of Subject Themes. Focussing on the recent history of English, and aiming to contribute to the diachronic characterisation of the medical genre, the study analyses the relation between the target audience and the thematic choices made by the writers. Following Berry (1995, 2013), Theme is understood as everything that comes up to the main verb of the clause, although we will be focussing on one part of it only, the syntactic Subject. As regards the meaning of (Subject) Themes, we propose a categorisation based on Berry's (2013) distinction between contentful and contentlight Subject Themes, and Prince's (1981: 237) assumed familiarity scale. Berry's (2013: 259) hypothesis that most Subject Themes are contentful in formal written texts, while most of them are contentlight in informal spoken texts is taken as a guiding benchmark. The consideration of Prince's (1981) scale is, in turn, an attempt to provide more delicate categorisations. The study tests to what extent the target audience is also a factor affecting the content weight of the thematic position or what the Subject Themes refer to. The data are taken from the electronic Corpus of Early English Medical Writing (Taavitsainen and Pahta 2011). •Attention is paid to possible interconnections between the linguistic features of Modern English medical texts and their intended target audiences.•A fine-grained scale of contentfulness is proposed for the categorisation of Subject Themes.•There seems to be a tendency for Subject Themes in texts addressed to learned audiences to be more contentful than those in texts addressed to intermediate and unlearned audiences.